PERBANDINGAN KOMPONEN KIMIA PENYUSUN MINYAK ATSIRI SIRIH LIAR {Piper ornatum) YANG BERASAL DARI SULAWESI SELATAN DAN PULAU SERAM DENGAN SIRIH BIAS A (Piper betle) - Sri Budi Sulianti; Chairul Chairul (BERITA BIOLOGI, 2002)
Comparison study on the chemical components of P. ornatum (Piperaceae) volatile oil, collected from Enrekang (South Celebes)and Sepa Village (Ceram Island, Moluccas) had been carried out by water distillation and Gas Chromatography-Mass Spectrometry (GC-MS) analysis. Those plants had exotic performance. The sample from South Celebes had original red color leaves and strong aromatic smell, but one from Ceram Island has green color leaves and weak aromatic smell. The results showed that volatile oil content of P. ornatum from Enrekang has higher than Sepa Village (0.94% and 0.81%), while the volatile oil of common piper (P.betle) was around 0.9-1.2%. GC-MS analysis determined that volatile oil of P. ornatum had 22 chemical components. Both volatile oil indicated similar peak fragmentation, in different intensities. The major component of P. betle and P. ornatum was caryophyllene i.e. 30.01% in the red leaf, 29.41% in the green leaf and 31.05% in P. betle. Some of minor components of P.ornatum were different, from P. betle.